First Report of Verticillium dahliae on Squash (Cucurbita pepo) in Italy - Stravato, V M (Plant disease, 2009)
During field surveys in February and March of 2007 and 2008, unusual symptoms of wilting were observed on squash plants (Cucurbita pepo L.) cultivated near Fondi (Latium-Central Italy) in two commercial plastichouses. Because of the high incidence of the disease (between 20 and 30%), we performed specific diagnostic assays. Symptoms included yellowing, stunting, vascular discoloration, and premature death of leaves. A fungus was consistently isolated on potato dextrose agar (PDA) from discolored vascular tissues in the stems. On the basis of fungal morphology (one-celled conidia, 1 to 2 μm in diameter, and produced on verticillate conidiophores), the fungus was identified as Verticillium dahliae Kleb. (1). To verify the pathogenicity of three fungal isolates, 2-week-old seedlings (15 plants per isolate) were inoculated by dipping the roots in a suspension of 105 conidia per ml for 30 s. Inocula were obtained from 2-week-old fungal cultures grown on PDA at 20 ± 2°C. Roots of 15 control plants were dipped in water. The seedlings were transplanted into pots containing peat and river sand (1:1, v/v) and placed in a greenhouse at 20 to 25°C. One month after inoculation, all fungal isolates caused wilting, while no symptoms were observed on control plants. The morphological features of the reisolated fungus, obtained only from the inoculated plants, were identical to the original isolates. V. dahliae has been recorded in Italy on a number of other plants (1,2). To our knowledge, this is the first report of V. dahliae on squash in Italy. Recently, V. dahliae was recorded for the first time on C. pepo L. in Trinidad (3). References: (1) M. Cirulli. L'Italia Agricola 112:120, 1975. (2) A. Matta et al. Inf. Fitopatol. 30:5, 1980. (3) S. N. Rampersad. Plant Dis. 92:1136, 2008